Misdiagnosed Arterio-Venous Malformation Causing Massive Bleeding Following Tooth Extraction in A Child: Case Report And Review of The Literature - Schütz, Petr; Bošnjaković, Petar; Lazović, Lazar; Al Sarraf, Lamiya (British Journal of Healthcare and Medical Research, 2023)
Arteriovenous malformations (AVMs) are rare, mainly high-flow lesions, comprising a complex network of primitive vessels with interconnecting feeding arteries and draining veins. Their clinical course varies, and while some AVMs are asymptomatic, others cause life-threatening complications. We describe the case of a tooth extraction from the area of misdiagnosed mandibular AVM in a child that caused life-threatening bleeding. After the emergency surgical intervention, the lesion was successfully managed by intravascular embolization